Transfer station cracks induced by cutting anchor cables and crack stabilization: A case study. (August 2021) - Zheng, Keyue; Shi, Chenghua; Lin, Yuexiang; Lei, Mingfeng; Liu, Jianwen
Highlights: Transfer station cracks induced by cutting anchor cables are studied. Field monitoring and numerical simulation are used for crack mechanism investigation. Crack repair and grouting methods are applied to prevent further cracking. Research results show that the crack stabilization methods worked effectively. Lessons learned from this incident have been presented. Abstract: This study reports an investigation on transfer station cracking induced by cutting anchor cables at North Yuehu Park station in Changsha city through both field monitoring and numerical simulation. The incident was triggered by cutting part of the original anchor cables while excavating a deep groove for an entrance diaphragm wall. When part of these support structures were removed, the stress condition of the station changed significantly, which eventually resulted in a large area of cracks. Crack repair and foundation pit bottom grouting were applied to prevent further cracking and resume the stability of the station, which achieved the desired result. The mechanisms of station cracking and the effectiveness of stabilization are investigated through both numerical simulation and field monitoring data analysis. In addition, an optimization scheme for station design is proposed and verified through numerical analysis. The lesson to be learned is that cutting the original anchor cables and structures of a sharp corner should be avoided during station construction. A reinforcement and field monitoring system should be implemented in advance to guarantee the safety of the station if cutting the original anchor cables is unavoidable.